Dynamic Branding : responsive and adaptive graphics for brands of today. (Hong Kong : Viction Workshop Ltd, 2024)
In an increasingly digital world, brands are faced with the challenge of reshaping their identities in order to solidify their presence both online and offline, not to mention in a variety of other mediums. As a result, many designers and creatives have chosen to break with the notion of “never change your identity” and have opted for fluid, adaptive graphics that flexibly adapt to each platform they are placed on. Interweaving elements that span across graphics, motion, and more, Dynamic Branding showcases the best examples of graphic systems that skillfully shapeshift across mediums to bring out the best of what their brand has to offer while maintaining its integrity and core values.
Keywords: Branding; Graphic design